Problematika Eksekusi Putusan Perdata Pasca Implementasi E-Court dan E-Litigation di Indonesia - Abd. Rahman Saleh (Lembaga Pengembangan Kinerja Dosen, 2026)
Judicial digital transformation through the implementation of e-Court and e-Litigation represents a strategic initiative of the Supreme Court of Indonesia to establish a modern, effective, and efficient judiciary. These innovations have successfully transformed various stages of civil case administration and litigation into faster and more transparent processes. However, the success of digitalization in case examination has not been accompanied by similar reforms in the execution of court judgments. This study aims to analyze the regulation of civil judgment execution following the implementation of e-Court and e-Litigation, identify challenges encountered in practice, and formulate a concept of execution digitalization as part of judicial reform. This research employs a normative legal method using statutory, conceptual, and case approaches. The legal materials consist of primary legal sources in the form of legislation and Supreme Court regulations, as well as secondary legal sources including scholarly literature and previous studies. The findings reveal that although e-Court and e-Litigation have accelerated dispute resolution processes, the execution of civil judgments remains largely conventional. Consequently, several challenges persist, including delays in execution, lack of transparency, and limited supervision by litigating parties. Therefore, the development of an integrated Digital Execution System linked to existing electronic judicial platforms is necessary to enhance the effectiveness of judgment enforcement and ensure greater legal certainty for justice seekers.